The JCMT nearby galaxies legacy survey – X. Environmental effects on the molecular gas and star formation properties of spiral galaxies. Issue 4 (9th January 2016) - Mok, Angus; Wilson, C. D.; Golding, J.; Warren, B. E.; Israel, F. P.; Serjeant, S.; Knapen, J. H.; Sánchez-Gallego, J. R.; Barmby, P.; Bendo, G. J.; Rosolowsky, E.; van der Werf, P.
Abstract: We present a study of the molecular gas properties in a sample of 98 H i – flux selected spiral galaxies within ∼25 Mpc, using the CO J = 3 − 2 line observed with the James Clerk Maxwell Telescope. We use the technique of survival analysis to incorporate galaxies with CO upper limits into our results. Comparing the group and Virgo samples, we find a larger mean H2 mass in the Virgo galaxies, despite their lower mean H i mass. This leads to a significantly higher H2 to H i ratio for Virgo galaxies. Combining our data with complementary Hα star formation rate measurements, Virgo galaxies have longer molecular gas depletion times compared to group galaxies, due to their higher H2 masses and lower star formation rates. We suggest that the longer depletion times may be a result of heating processes in the cluster environment or differences in the turbulent pressure. From the full sample, we find that the molecular gas depletion time has a positive correlation with the stellar mass, indicative of differences in the star formation process between low- and high-mass galaxies, and a negative correlation between the molecular gas depletion time and the specific star formation rate.